2011
DOI: 10.1111/j.1468-3083.2010.03791.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of stem cell markers nestin and cytokeratin 15 and 19 in cutaneous malignancies

Abstract: Our study described the expression profiles of stem cell markers CK15, CK19 and nestin in BCC, SCC and MCC. In addition to confirming results of the previous reports, our study also showed positive nestin expression in around half of SCC cases, which adds this malignancy to the cutaneous tumours that have been so far reported to exhibit nestin expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
42
4

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 41 publications
9
42
4
Order By: Relevance
“…Our study demonstrated that the majority of BCC samples expressed low levels of CD133 and Nestin which is in line with previous reports that indicated low or no expression of CD133 and Nestin in BCC tumors (Abbas O and Bhawan, 2011).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our study demonstrated that the majority of BCC samples expressed low levels of CD133 and Nestin which is in line with previous reports that indicated low or no expression of CD133 and Nestin in BCC tumors (Abbas O and Bhawan, 2011).…”
Section: Discussionsupporting
confidence: 93%
“…Our findings were in agreement with those of previous studies indicating that melanoma samples expressed higher level of CD133 and Nestin than non-melanoma skin cancers (Monzani et al, 2007;Sharma et al, 2010;Fusi et al, 2011).Our study demonstrated that the majority of BCC samples expressed low levels of Nestin and CD133, while some previous reports indicated no expression of Nestin in BCC cases (Florenes et al, 1994;Abbas O and Bhawan, 2011). This discrepancy could be due to the selection of different cut-off points and different experimental conditions.…”
Section: Discussionsupporting
confidence: 91%
“…Studies in mice demonstrate that CK15 positive cells can give rise to progeny that express CK5 (35). Besides its presence in cutaneous neoplasms (36,37), CK15 has also been found up-regulated in gene expression studies in SqCC of the lung (38,39) and in one MALDI imaging study on lung cancer samples (21). In our study, CK15 was a valid classifier of SqCC.…”
Section: Discussionsupporting
confidence: 66%
“…Epithelial membrane antigen is positive in MAC and helps differentiate from morphoeic BCC [ 40 ] . Staining for cytokeratin 15 may be useful in excluding basal-cell and squamous cell carcinoma but not desmoplastic trichoepithelioma [ 41 ] .…”
Section: Histopathological Featuresmentioning
confidence: 99%